Geriatric nutrition the health professional's handbook - Chernoff, Ronni (Burlington, MA Jones & Bartlett Learning, 2014)
A authoritative reference written to help professionals understand the role of nutrition in the maintenance of health, the management of chronic conditions, and the treatment of serious Illness. The fourth edition of this text provides a comprehensive review of nutritional assessment, intervention programs for the elderly, and health promotion activities.
Demographics of aging -- Protein metabolism and requirements -- Carbohydrate, fat and fluid requirements in older adults -- Vitamin nutriture in older adults -- Mineral requirements -- Trace metal requirements -- Smell, taste, and oral somatosensation : age-related changes and nutritional implications -- Oral health in elderly people -- Swallowing problems in older adults -- The aging gut -- Cardiovascular disease in older adults -- Aging and the kidney -- Impact of nutrition on the age-related declines in hematopoiesis -- Skeletal aging -- Endocrine aspects of nutrition and aging -- Pharmacology, nutrition, and elderly adults : interactions and implications -- The geriatric exercise prescription : nutritional implications -- Nutritional assessment of elderly results -- Nutritional support for the older adult -- A continuum of nutrition services for older Americans -- Health promotion and disease prevention in elderly adults.
Includes bibliographical references and index.
Keywords: Older people -- Nutrition